Preliminary survey from the antimicrobial resistance of Vibrio cholerae O1, epidemic outbreak 1998 - Ibarra, J. O. (2000)
Thirty strains of V. cholerae O1 Ogawa and 2 Inaba, isolated during the outbreak of 1998, were studied in relation to thier sensibility in front of 10 antibiotics of clinical use. Nine strains were determined (28.1%) resistant to 1 up to 6 antibiotics. The SIDS-PAGE of the studied strains exhibited similar pattern of bands.